Integration of Ligand-Based Drug Screening with Structure-Based Drug Screening by Combining Maximum Volume Overlapping Score with Ligand Docking - Yoshifumi Fukunishi; Haruki Nakamura (MDPI AG, 2012)
Ligand-based and structure-based drug screening methods were integrated for in silico drug development by combining the maximum-volume overlap (MVO) method with a protein-compound docking program. The MVO method is used to select reliable docking poses by calculating volume overlaps between the docking pose in question and the known ligand docking pose, if at least a single protein-ligand complex structure is known. In the present study, the compounds in a database were docked onto a target protein that had a known protein-ligand complex structure. The new score is the summation of the docking score and the MVO score, which is the measure of the volume overlap between the docking poses of the compound in question and the known ligand. The compounds were sorted according to the new score. The in silico screening results were improved by comparing the MVO score to the original docking score only. The present method was also applied to some target proteins with known ligands, and the results demonstrated that it worked well.